Impact of verbal abuse on social anxiety among female college students: A cross-sectional study - AlMusailhi, Jawaher; Aldulaijan, Fajar; Alabdulqader, Njood; Aldossari, Mae; Saleh, Maan; Abumadini, Mahdi; Al Ghamdi, Kholoud (Acta Biomedica Atenei Parmensis, 2024)
Background and aim. Social anxiety is defined as the feeling of intense discomfort when interacting with others. Verbal abuse is an unjust behaviour where people are exposed verbally to words that assault them and eventually affect their psychological health. This study investigates the prevalence of both social anxiety and verbal abuse among female college students. It also studies the association between verbal abuse and social anxiety. Methods. A cross-sectional study on 220 female college students. Liebowitz Social Anxiety Scale, and verbal abuse questionnaire were distributed to the participants. Results. Among the 220 participants, 26.4% had social anxiety and 61.4% showed evidence of verbal abuse. Forty percent of the verbally abused participants suffered from one form or another of social anxiety. Also, verbal abuse was found to be a significant predisposing factor for social anxiety (P<0.001). Conclusion. There is a relatively high percentage of verbal abuse and social anxiety among female college students. Also, verbal abuse may lead to social anxiety on the long-term. Raising awareness among regarding the long-term effects of verbal abuse is a very important issue to prevent its consequences not only on the verbally abused themselves, but also on their societies.